Research Progress in Viral Inactivation Utilizing Human Norovirus Surrogates - Kamarasu, Pragathi; Hsu, Hao-Yuan; Moore, Matthew D. (Frontiers in Sustainable Food Systems, 2018)
Human noroviruses are the leading cause of foodborne illness globally. Numerous challenges in control of these viruses exist due to multiple viral characteristics: the ability to environmentally persist for over a month; relatively low infectious dose; lack of extremely effective, non-corrosive inactivation agents; and considerable inhibitory effects of food matrices and organic loads observed with common use of promising inactivation agents. Although a major breakthrough in the field, recent in vitro human norovirus cultivation systems have been limited in their ability to be widely utilized for identification of promising inactivation agents. Thus, cultivable human norovirus surrogates remain the most readily utilizable models for studying the effect of various inactivation agents on viral infectivity. The purpose of this review is to highlight recent developments and reports related to norovirus surrogate inactivation with a special focus on the various degrees of food matrix-associated inhibition for different inactivation agents.